Henry and June - Nin, Anais, 1903-1977. (San Diego : Harcourt Brace & Co., 1989)
An account of Anais Nin's sexual awakening, this book describes her friendship with Henry Miller and his wife, June, and the fiery affair with Henry that liberated her sexually and morally, undermined her idealized marriage, and led her into psychoanalysis
"A Harvest book."
Includes index.
Keywords: Nin, Anais, -- 1903-1977 -- Diaries; Authors, American -- 20th century -- Diaries; Miller, Henry, -- 1891- -- Relations with women; Smith, June Edith